Comparison of irradiated feed and food grade spray-dried animal plasma on nursery pig performance - J C Woodworth; C W Hastad; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
Two experiments were conducted to determine the effects of initial bacterial concentrations in animal plasma on growth performance of weanling pigs. In Exp. 1 during the experimental period (d 0 to 14), pigs fed plasma had increased ADG and ADFI compared to pigs fed the control diet. Pigs fed the irradiated AP 920, as well as source 1 and source 2 regular (nonirradiated) food grade plasma had increased ADG compared to the control diet. Furthermore, pigs fed irradiated AP 920, regular AP 820, regular and irradiated source 1 food grade and regular source 2 food grade animal plasma had improved ADFI compared to pigs fed the control diet. No differences in F/G were observed between treatments. No differences were detected between pigs fed diets that contained irradiated plasma compared to those fed it in the regular form. For the overall experiment (d 0 to 24), pigs fed irradiated AP 920 had a tendency for improved F/G compared to pigs fed the control diet. In Exp. 2 during the experimental period (d 0 to 14), pigs fed diets containing plasma had improved ADG and F/G compared to pigs fed the control diet. Pigs fed irradiated AP 820 food grade plasma had higher ADG compared to pigs fed regular AP 820. For the overall experiment (d 0 to 24), pigs fed diets containing irradiated AP 820 had increased ADG, final body weight, and ADFI compared to pigs fed regular AP 820. Since irradiation of food grade plasma (low initial bacteria) did not improve growth performance while irradiation of feed grade plasma (initially high bacteria) improved performance, the initial bacteria level of animal plasma appears to influence growth performance of nursery pigs.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Nursery pigs; Animal plasma; Irradiation